Educational Methods and Technological Innovations for Introductory Experiential Learning Given the Contact-Related Limitations Imposed by the SARS-CoV2/COVID-19 Pandemic - Paul M. Reynolds; Erica Rhein; Monika Nuffer; Shaun E. Gleason (MDPI AG, 2021)
Background: Acute respiratory syndrome related coronavirus disease (COVID-19) has led to substantial changes in pharmacy curricula, including the ability to provide in-person introductory experiential practice experiences (IPPEs) to University of Colorado's International-Trained PharmD (ITPD) students. Methods: The IPPE course for ITPD students was redesigned to offer remote educational activities in the health system setting and simulated practice and communication activities in the community setting. Students were evaluated via surveys regarding the perceived value of these changes, and changes in knowledge, skills and abilities before and after activities. Results: A total of 6 students were enrolled in the revised IPPE course. Students agreed or strongly agreed that the overall distance-based IPPE experience, the remote health system activities, and the community activities were valuable. Students also strongly agreed that course design successfully met course outcomes and was relevant to pharmacy practice. In terms of knowledge, skills and abilities, numeric improvements were observed in remote health system activities and community-based simulated patient interactions, but results were not statistically significant. A high baseline level of knowledge led to minimal improvements in perceptions of improvement in community pharmacy skills regarding pharmacy simulation software. Conclusion: Implementation of distance-based IPPE activities may be an alternate educational modality.